KREATIVITAS ANAK USIA DINI PERSPEKTIF PROGRESIVISME - Diah Anika Fahrani; Sudjarwo, Sudjarwo; Bujang Rohman; Muhammad Nurwahidin (Jurnal Cakrawala Ilmiah, 2022)
The purpose of this study is to find out what creativity is, the importance of the aspect of creativity in early childhood, the important role of the teacher as a facilitator in encouraging creativity and the linkage of creativity based on the perspective of progressivism. As is known, a common occurrence to date is the existence of a number of problems which show that there are still many individuals who are unable to present their work in real or real terms; the majority of these individuals prefer to duplicate the work of others. The inability to develop a work is an indication of a lack of imagination. Creativity is not a foreign concept for children studying in kindergarten or PAUD, because everything they do in kindergarten and early childhood is basically creative. Therefore, teachers and parents should realize the importance of creativity for the survival of their children starting with their earliest education. Education is an effort to grow and develop the characteristics of intelligence, skills, and character of students, which is carried out in stages. All forms of education, including early childhood education, must be implemented based on the philosophy of education. The flow of progressivism is one of the educational understandings of the existence of a flow in education that supports change or progress in the application of education. The writers do library research of this type (library research). The creativity of early childhood, as viewed through the lens of progressivism, is bolstered by associated theories, which are designed to provide readers with information that may be implemented in the everyday education of children.